Secure Internet of Things Device with Single-Channel Communication for Resource-Constrained Applications - Ankur Gupta; Sahil Sawhney; Suhaib Ahmed (Engineering Proceedings)
Internet of Things (IoT) devices are being utilized in large numbers in various applications, ranging from healthcare, manufacturing, and home automation to manufacturing, etc. This rapid increase in the number of devices has also led to a significant increase in cybersecurity concerns for these devices. Malicious nodes exploit vulnerabilities in conventional IoT architectures, leading to high risks to data integrity, privacy, and system reliability. Hence, there is a need for innovative solutions to improve the security of IoT devices and networks. Considering this, in this paper, a novel approach towards securing IoT devices against any malicious attack is proposed. A new IoT node is proposed, that has a single communication channel, which sends information only to a specific endpoint. Unlike a conventional IoT system with multiple communication channels, the proposed design limits communication to a single dedicated device, thereby drastically reducing the attack probability. The proposed device architecture integrates a robust cryptographic protocol to establish a secure and authenticated communication link between the IoT device and its designated endpoint. By employing a state-of-the-art encryption technique and secure access controls, the proposed solution can mitigate common attacks such as eavesdropping, data tampering, and unauthorized access. The proposed system also improves resource efficiency, lowers the device’s power consumption due to single-communication-channel data transmission, and simplifies network management, thus making it suitable for resource-constrained applications, such as military surveillance, home automation, etc.